Competitive School Culture Management in Cultivating Teacher Creativity and Innovation at SMA Negeri 2 Plus YPMHB Sipirok - Sugesti, Tutik; Siregar, Astri Novia (Jurnal Riset Ilmu Pendidikan, 2025)
This study aims to explore the management of competitive school culture in fostering teacher creativity and innovation at SMA Negeri 2 Plus YPMHB Sipirok. Competitive school culture is considered as one of the important factors in encouraging teacher professional development, which in turn can improve the quality of learning. This study uses a qualitative approach with data collection techniques in the form of in-depth interviews, observations, and documentation studies. The results of the study indicate that the management of competitive school culture at SMA Negeri 2 Plus YPMHB Sipirok includes strategies such as improving teacher professionalism through continuous training, collaboration between teachers, and giving awards to innovative teachers. However, there are challenges such as resistance to change, limited resources, and high workloads that hinder the implementation of a competitive culture to the maximum. In the discussion, this study emphasizes the importance of the role of transformational leadership in creating a climate that supports creativity and innovation, as well as the need for external support to overcome existing obstacles. Based on these findings, it is recommended that schools continue to strengthen the management of competitive culture by paying attention to supporting factors such as relevant training, adequate resources, and reducing administrative barriers, in order to create a more innovative and creative environment among teachers